Determination of Reference Dose (RfD) of mercury exposure based on NOAEL mercury - Tualeka, Abdul Rohim; Rifky, Mahmud Aditya; Jalaludin, Juliana; Russeng, Syamsiar S; Rahmawati, Pudji; Ahsan, Ahsan; Susilowati, Indri H (Universidad del Zulia, 2019)
This study aimed to determine the RfD from mercury exposure in Bulawa Subdistrict in Bone Bolango District using NOAEL mercury in white mice and body weight and height of Indonesians who were exposed to mercury.This wasan observational study with a cross-sectional design using manual quantitative data analysis methods. As a result, the average mercury concentration in respondents’ drinking water and fish consumed was 0.000478 mg/L and 0.0298 mg/kg. In conclusion,the average mercury concentration in respondents’ drinking water and fish consumedis still below the threshold limitvalue set by the national standard for mercury concentrations